1998
DOI: 10.1080/11250009809386828
|View full text |Cite
|
Sign up to set email alerts
|

Diet composition and size‐related changes in the feeding of pikeperch,Stizostedion lucioperca(Percidae) and pike,Esox lucius(Esocidae) in the Lake Peipsi (Estonia)

Abstract: The aim of this study was to estimate the composition of the diet and size-related changes in the prey selection of pikeperch and pike in L. Peipsi. A total of 591 pikeperches with a standard length (Sl) of 9-73 cm and 254 pikes (Sl = 25-105 cm) were sampled with a bottom seine and an experimental trawl in 1994-1996 and their stomach content analysed. The frequency of occurrence and number of prey fish per individual were used for the description of the diet. The recent diet of pikeperch and pike in the Lake P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
27
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 10 publications
2
27
0
Order By: Relevance
“…Besides, insectivorous feeding was also observed at low ratio. Similar feeding habits have been observed in several different habitats (Kangur & Kangur, 1998;Lorenzoni et al, 2002;Amundsen et al, 2003;Persson, Bertolo, & De Roos, 2006). However, the diet of pike inhabiting different habitats has a broad prey food types from invertebrates to vertebrates including mammalian prey (Sammons, Scalet, & Neumann, 1994;Elvira, Nicola, & Almodovar, 1996;Soupir et al 2000;Liao, Pierce, & Larscheid, 2002).…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…Besides, insectivorous feeding was also observed at low ratio. Similar feeding habits have been observed in several different habitats (Kangur & Kangur, 1998;Lorenzoni et al, 2002;Amundsen et al, 2003;Persson, Bertolo, & De Roos, 2006). However, the diet of pike inhabiting different habitats has a broad prey food types from invertebrates to vertebrates including mammalian prey (Sammons, Scalet, & Neumann, 1994;Elvira, Nicola, & Almodovar, 1996;Soupir et al 2000;Liao, Pierce, & Larscheid, 2002).…”
Section: Discussionmentioning
confidence: 75%
“…In contrast, Chapman et al (1989) indicated that foraging on invertebrates was not limited to smaller pike and instead that invertebrates were found in the stomach of 24-60 cm standard body length pike from several lakes in Canada. The several studies also found size-related changes in the feeding of different pike populations (Mann, 1982;Eklöv & Hamrin, 1989;Sammons et al 1994;Kangur & Kangur, 1998;Çubuk et al 2006). This change based on length may be result from maximum energy requirement and gape-size limited in predator.…”
Section: Discussionmentioning
confidence: 99%
“…That the pike is a piscivorous predator has been demonstrated in numerous studies which showed a predominance of fish in the diet beginning at an early age (AVIAN et al, 1998;FILLEUL and LE LOUARN, 1998;KANGUR and KANGUR, 1998). However in Lake Trasimeno the pike's diet is varied and not exclusively fish-based, but fish were more important in its diet than for largemouth bass.…”
Section: Discussionmentioning
confidence: 99%
“…The degree of diet overlap was calculated by separating the specimens into classes based on length (SCOTT and ANGERMEIER, 1998): TL < 25 cm and TL > 25 cm for M. salmoides and TL < 40 cm and TL > 40 cm for E. lucius. The choice of length classes was based on the ontogenetic changes of the diet as reported in literature (MACEINA and MURPHY, 1988;RAAT, 1988;GODINHO and FERREIRA, 1994;HICKLEY et al, 1994;NICOLA et al, 1996;KANGUR and KANGUR, 1998).…”
Section: Methodsmentioning
confidence: 99%
“…Fish become dominant in the pikeperch diet beginning in the second year of life (Lehtonen et al, 1996). However, pikeperch are opportunistic feeders (Salonen et al, 1996), and dietary composition may vary among areas (Kangur and Kangur, 1998). For example, smelt and perch are the most important dietary items of pikeperch in boreal lakes (Peltonen et al, 1996;Vehanen et al, 1998).…”
Section: Discussionmentioning
confidence: 99%